The Seafood Restaurant Industry's Big Success? - Suryawan, Ian Nurpatria (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
Innovative performing behaviour depends on the employee's personality; becoming innovative is the behaviour of an employee to create, recognise, and implement something new and bring profit to the company. Leaders' styles can be essential to increasing innovation in their work. This study was conducted at five seafood restaurants in North Jakarta with 60 respondents. Purposive sampling was the method of sampling. The questionnaires were distributed from early January 2024 to the end of January 2024. data were analysed using path analysis statistical tools. The target criteria for this research are employees from the staff level to middle-level managers from seafood restaurants who have worked for at least two years. This research shows that motivation and innovation performance do not significantly affect employee performance; the most influential factor in this study is the leader style.